EFEKTIVITAS PEMUNGUTAN PAD DAN KONTRIBUSINYA PADA PENDAPATAN DAERAH - Laksmi, Sonia Wina; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2014)
Regional autonomy is authority of local governments to explore its potential improve the fiscal capacity the capital the regional administration. PAD is one of the sources of financing of the most important areas to promote and develop areas interest to many people. PAD is expected to provide largest contribution the Local Revenue. This study aims to determine effectiveness and contribution revenue collection at Regional Income Gianyar regency. Data collection methods used were nonparticipant observation. The variable in this study is the ratio the effectiveness and contribution ratio. Based on the analysis, the effectiveness revenue collection in Gianyar years 2009-2013 based effectiveness ratio of 115.20 percent can be categorized very effective, and the ratio of the contribution in 2009 amounted to 15.79 per cent, in 2010 amounted to 19.90 per cent, belong the category of less good, than in 2011-2013 amounted to 23.75 percent, 24.50 percent, and 25.60 were classified categories
Keywords: effectiveness , contribution , local revenue